Spatial Modeling for Determining Managerial Options for Structuring Productivity in KPH Bogor - Ricca Rohani Hutauruk; Nining Puspaningsih; Muhammad Buce Saleh (Institut Pertanian Bogor (IPB University), 2016)
KPH Bogor Ricca Rohani Hutauruk1, 2*, Nining Puspaningsih3, Muhammad Buce Saleh31Graduate School of Bogor Agricultural University, Dramaga Main Road, Campus IPB Dramaga, Bogor,Indonesia 16680 2Trainer, Environment and Forestry Education and Training Bogor Agency,The Ministry of Environment and Forestry, Jl. Prada Samlawi Rumpin, Bogor, Indonesia 3Department of Forest Management, Faculty of Forestry, Bogor Agricultural University, Academic Ring Road,Campus IPB Dramaga, PO Box 168, Bogor, Indonesia 16680Received Agustus 23, 2016/Accepted October 20, 2016AbstractIn the past few years, forest management unit (KPH) Bogor has experienced many problems, technical, environmental and social, affecting the company's finances. This condition requires new breakthroughs in the form of managerial options in managing the forests of KPH Bogor. At present, KPH Bogor has formulated 12 managerial options. The purpose of this study is to build a spatial model in selecting managerial options at site level. The spatial models were built based on the score of each land unit which was obtained from expert judgment using an intensity scale, while weight was obtained using a pairwise comparison, resulting in the following equation: total score = 0.14 (0.06x1 + 0.11x2 + 0.09x3 + 0.08x4 + 0.10yx5 + 0.31x6 + 0.25x7) + 0.72 (0.08y1 + 0.22y2 + 0.46y3 + 0.13y4 + 0.12y5) +0.14 (0.45z1 + 0.05z2 + 0.44z3 + 0.06z4). The resulting total score was then divided into 5 classes using the equal interval method. The results for each of the managerial options were then aggregated using GIS to create KPH Bogor's management pattern. In areas where there was an overlap due to the similarity in options, a decision support system using neighboring similarity spatial analysis was used. This step allowed the spatial model to be built with many biophysical, social, and economic variables. This spatial model could map 12 types of managerial options at site level in the production structuring in KPH Bogor.